Clinics in diagnostic imaging (78). Cardiac rhabdomyoma in tuberous sclerosis - Visrutaratna P. (2014)
A seven-day-old boy with a family history of tuberous sclerosis presented with congestive heart failure. Cardiac-gated magnetic resonance (MR) imaging showed a mass in the right atrium, which was T1-isointense and T2-hyperintense relative to myocardium. Follow-up echocardiographical studies showed a decrease in the number and size of the nodules. Finally, no cardiac nodules were seen when he was two years and eleven months old. The echocardiographical studies, MR imaging findings and the clinical history are consistent with cardiac rhabdomyomas. MR imaging of the brain also showed multiple subependymal nodules, white matter abnormalities, and cortical tubers. The varied imaging appearances of tuberous sclerosis are discussed and illustrated with additional examples.